Iatrogenic Neonatal Esophageal Perforation: A European Multicentre Review on Management and Outcomes - Eva Sorensen; Connie Yu; Shu-Ling Chuang; Paola Midrio; Leopoldo Martinez; Mathew Nash; Ingo Jester; Amulya K. Saxena (MDPI AG, 2023)
Background: The aim of this multicenter retrospective study and literature review was to review management and outcomes of neonatal esophageal perforation (NEP). Methods: Protocol data were collected from four European Centers on gestational age, factors surrounding feeding tube insertion, management and outcomes. Results: The 5-year study period (2014-2018) identified eight neonates with median gestational age of 26 + 4 weeks (23 + 4-39) and median birth weight 636 g (511-3500). All patients had NEP from enterogastric tube insertions, with the perforation occurring at median 1st day of life (range 0-25). Seven/eight patients were ventilated (two/seven-high frequency oscillation). NEP became apparent on first tube placement (n = 1), first change (n = 5), and after multiple changes (n = 2). Site of perforation was known in six (distal n = 3, proximal n = 2 and middle n = 1). Diagnosis was established by respiratory distress (n = 4), respiratory distress and sepsis (n = 2) and post-insertion chest X-ray (n = 2). Management in all patients included antibiotics and parenteral nutrition with two/eight receiving steroids and ranitidine, one/eight steroids only and one/eight ranitidine only. One neonate had a gastrostomy inserted, while in another an enterogastric tube was orally successfully re-inserted. Two neonates developed pleural effusion and/or mediastinal abscess requiring chest tube. Three neonates had significant morbidities (related to prematurity) and there was one death 10 days post-perforation (related to prematurity complications). Conclusions: NEP during NGT insertion is rare even in premature infants after evaluating data from four tertiary centers and reviewing the literature. In this small cohort, conservative management seems to be safe. A larger sample size will be necessary to answer questions on efficacy of antibiotics, antacids and NGT re-insertion time frame in NEP.